Analytics by Anova in Clinical Predictions - R, Jamuna (International Journal of Computer Sciences and Engineering, 2019)
Diabetes is a dreadful disorder facing the mankind from children to the older people irrespective of their age. This paper gives a mathematical model and analytics of different types of the diabetic population with different types medical managements. Diabetes is mainly a pancreatic disorder where there is insufficient secretion of insulin or improper functioning in the utilization of insulin for Glucose metabolism. Mainly there are five types of diabetes disorders such as Type-1, Type-2, Gestational diabetes, Juvenile diabetes and, MODY diabetes. In the sample population taken for study, these various types of the pancreatic disorders can be brought under control by medical managements like Allopathy, Siddha, Homeopathy and Ayurvedic treatments. The paper statistically analyses the diabetic population for number of patients under controls in various types of medical management by a mathematical model. Null hypothesis assumes that the numbers of paients under control of diabetes in various managements are independent of the type of treatments given by allopathy and other alternative methods. The powerful statistical tool ANOVA finds if there is significant difference between class means in view of variability within the separate classes. ANOVA method is used to analyze the sample population and the null hypothesis assumes that the number of patients with different level of controls is the same for different types of treatments in the sample diabetic population. The calculated value of variance ratio F is > the table value at 5% level. So the null hypothesis may be rejected at 5% level of significance. It gives an inference that there is significant difference between treatments given by various methods like allopathy, siddha, ayurvedic, homeopathy in the level of control for patients. Even though diabetes can never be cured by any method but can be kept under control to avoid complications in major organs.